Kristeva’s Ontological Approach to Limit and Secondary Identification with the Mother - Angelova, Emilia (Acta Nova Humanistica: A Journal of Humanities Published by New Bulgarian University, 2024)
I propose an ontological approach via Hegel to Kristeva's notion of archaic loss, specifically her theory of secondary identification with the mother. I argue that she elaborates the pre-Oedipal relation to the mother as part of the presupposition that Hegel's Modernity realizes history's empty transmission of trauma. Trauma functions as a critique of dialectic in crisis, by Derrida and Nancy, on the basis of Hegel's work of loss and the return of loss "for us." Because of Kristeva's work on the semiotic and signification, the implication of ontological loss in this approach also allows her to develop especially her view of sublimation in divergence, from Lacan's approach to Antigone and the limit of the human.